2020
DOI: 10.3390/agronomy10060762
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Root-Lesion and Stunt Nematodes, and Their Relationship with Soil Properties and Nematode Fauna in Sugarcane Fields in Okinawa, Japan

Abstract: Sugarcane cultivation in Japan has not yet focused on suppressing plant-parasitic nematodes. For proper nematode management, it is essential to know the spatial distribution of economically important plant-parasitic nematodes and free-living nematodes that play important roles in terrestrial ecosystems. We aimed to reveal nematode fauna and soil properties in 85 sugarcane fields of three major sugarcane producing islands in Japan, and to examine their relationship by using the mixed-effect model and by visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Pratylenchus sp. abundance was reported to be negatively correlated with pH, suggesting that Pratylenchus may be more abundant at lower than higher pH (Spaull et al, 2001;Kawanobe et al, 2020). Previous studies have shown that Pratylenchus abundance is significantly influenced by soil texture (Griffin, 1996).…”
Section: Figmentioning
confidence: 97%
“…Pratylenchus sp. abundance was reported to be negatively correlated with pH, suggesting that Pratylenchus may be more abundant at lower than higher pH (Spaull et al, 2001;Kawanobe et al, 2020). Previous studies have shown that Pratylenchus abundance is significantly influenced by soil texture (Griffin, 1996).…”
Section: Figmentioning
confidence: 97%
“…Barros et al (2005) As flutuações populacionais dos nematoide no tempo variam dependendo de fatores como perfil do solo, temperatura e precipitação (Silva et al, 2021). Cunha et al (2020) Diversos estudos afirmam que a distribuição da comunidade de nematoides em cana planta e em soqueiras, são menores no início do cultivo da cana planta, aumentando ao longo das sucessivas socas (Campos et al, 2006;Kawanobe et al, 2020), embora aumentos populacionais possam ocorrer ao longo do ciclo de cultivo em função de vários fatores, principalmente da umidade do solo e da temperatura (Santos et al, 2022;Hussain et al, 2019). Contudo, estudos sobre a dinâmica da comunidade de nematoides no solo nas condições do nordeste brasileiro durante as fases de cultivo da cana planta como, por exemplo, brotação, perfilhamento, crescimento vegetativo dos colmos e maturação são escassos (Oliveira et al, 2011).…”
Section: Análise Estatísticaunclassified
“…After finding an appropriate host, RKN J2s readily perforate below the root's protraction zone, migrate between cells toward the root tip, and pass the Casparian strip to reach the vascular tissue (Shukla and Barberon North Sinai Korayem et al (2014) 2021). The specific signals that govern the direction of J2s in the roots are uncertain, and only the role of CO 2 as a significant attractant is known (Banerjee and Hallem 2020); however, pH can also influence the direction in which the J2s migrate (Kawanobe et al 2020). Root-knot nematodes release a combination of enzymes that degrade the cell wall, which they use to transmit and split the soft, intermediate lamella connecting the root cells (Rai et al 2015).…”
Section: Life Cycle Of Root-knot Nematodesmentioning
confidence: 99%